Analisis Kinerja Keuangan PT Bank BNI Syariah 2020 dan Rekomendasi Kebijakan Ekonomi Islam untuk Meningkatkan Kesejahteraan pada Masa Pandemi Covid-19 - Salwa, Aqmarina Maulida; Caesarli, Dinda; Silviani S, Dwi Ratna (Diponegoro Journal of Islamic Economics and Business, 2021)
The COVID-19 pandemic is an epidemic desease that have attacked this world recently, incluidng Indonesia. The virus also affect almost all sectors in this life, especially Islamic banking financial system. With the exponential speed of spread the effort to save both health and economic aspect become essential. This study aims to analyse the financial performance of Islamic banks and the role of its kind of banks in economic policy during covid pandemic. By using systematic literature review, the result shows that financial performance of BNI syariah bank in 2020 is in healthy condition facing the risk of the pandemic. The average value of ROA is 1.3% and ROE is 9.97% which means it is quite healthy. Then the average NPF ratio is 3.38% that also show the healthy condition, while the average CAR ratio is 21.4% and also BOPO that shows 84,1% that is categorised as very healthy. As Islamic bank has resilience in the pandemic era , it is better for regulators to make regulation to islamic bank to  increase more rapidly and hopefully can boost recovery of economic condition when the country faces crisis again.